2021
DOI: 10.1016/j.thromres.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk of symptomatic venous thromboembolism in mild and moderate COVID-19: A comparison of two prospective European cohorts

Abstract: Background: Severely ill patients with SARS-CoV-2 have an increased risk of venous thromboembolism (VTE) i.e., deep vein thrombosis and pulmonary embolism. However, the VTE risk in patients with mild and moderate COVID-19, hospitalized or managed at home, remain uncertain. The aims of this study were to assess the rate and the risk factors symptomatic VTE, in patients with mild and moderate COVID-19 and to compare them to a cohort of similar patients without COVID-19. Methods: Patients presenting to the emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
2
4
0
2
Order By: Relevance
“…Coagulopathies [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102], and especially the formation of extensive microclots in vivo, are a hallmark of both COVID [85,[103][104][105][106][107][108][109][110][111][112][113][114][115] and long COVID [116,117], and we have demonstrated that these microclots too are amyloid in character [108,109,116]. Importantly, the addition of purified, recombinant SARS-CoV-2 S1 spike protein to coagulation-competent normal plasma is sufficient to induce the formation of anomalous clots [118] that adopt amyloid states that are also resistant to fibrinolysis [108].…”
Section: Amyloid Fibrin Microclots (Fibrinaloids) In Covid-19 and Lon...mentioning
confidence: 67%
“…Coagulopathies [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102], and especially the formation of extensive microclots in vivo, are a hallmark of both COVID [85,[103][104][105][106][107][108][109][110][111][112][113][114][115] and long COVID [116,117], and we have demonstrated that these microclots too are amyloid in character [108,109,116]. Importantly, the addition of purified, recombinant SARS-CoV-2 S1 spike protein to coagulation-competent normal plasma is sufficient to induce the formation of anomalous clots [118] that adopt amyloid states that are also resistant to fibrinolysis [108].…”
Section: Amyloid Fibrin Microclots (Fibrinaloids) In Covid-19 and Lon...mentioning
confidence: 67%
“…After adjusting for comorbid conditions, patients in the moderate cohort had an absolute increase in risk for thrombosis of 1.69%. 32 …”
Section: Discussionmentioning
confidence: 99%
“…2 These thromboses are primarily venous, although arterial thromboses have been described, 4 and there is a clear association between the presence and extent of thrombosis and the severity of the illness. [5][6][7] Hence, considerable research has focused on how the SARS-CoV-2 virus interacts with the blood clotting system 8,9 in conjunction with the endothelium 3,10 to promote thrombosis. The AstraZeneca vaccine, in particular, has also been associated with the formation of venous thromboses, 11 although at a much lower incidence.…”
Section: Discussionmentioning
confidence: 99%